Crosslinked polyethylene/polypyrrole nanocomposites with improved direct current electrical characteristics. (October 2018) - Zhang, Chengcheng; Zhang, Hongyu; Li, Chunyang; Duan, Sixu; Jiang, Yang; Yang, Jiaming; Han, Baozhong; Zhao, Hong
Abstract: Space charge accumulated in insulation materials could result in local field distortion, accelerate the material aging and threaten the security of high voltage direct current (HVDC) cable. To suppress the space charge accumulation and improve the direct current (DC) electrical characteristics of crosslinked polyethylene insulation materials, crosslinked polyethylene/polypyrrole (XLPE/PPy) nanocomposites were prepared, and the DC conduction and breakdown strength were investigated. The XLPE/PPy nanocomposites were characterized by Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). The DC electrical characteristics measurement results showed that the introduction of nano-polypyrrole (nano-PPy) could reduce the DC electrical conduction current density of XLPE/PPy nanocomposites, improve the space charge distribution but not affect the crosslinking reaction and crystallinity of XLPE. While assuring excellent electrical conduction and space charge distribution characteristics, there was an optimum nano-PPy content to reduce the DC breakdown strength of XLPE/PPy nanocomposites insignificantly. Highlights: PPy nanobowls in the doped state have been prepared successfully. The introduction of nano-PPy would not affect the crossliking reaction and crystallinity of XLPE. Nano-PPy could create deep traps and suppress space charge accumulation. The introduction of nano-PPy could reduce DC electrical conduction current density. XLPE/PPy nanocomposites with 0.2 phr nano-PPy had excellent DC electrical characteristics.